Comparison of clinical outcomes in all-arthroscopic versus mini-open repair of rotator cuff tears: A randomized clinical trial. Issue 11 (March 2017) - Liu, Jin; Fan, Lin; Zhu, Yingbo; Yu, Haotong; Xu, Tianyang; Li, Guodong
Abstract: Background: The aim of the study was to compare the clinical outcomes of patients undergoing all-arthroscopic (AA) or mini-open (MO) rotator cuff repair. Methods: The present study evaluated 50 patients who had undergone AA repair and 50 patients who had undergone MO repair with a minimum 1-year follow-up. Every patient was asked to complete the Disabilities of the Arm, Shoulder and Hand (DASH) and visual analog scale (VAS) questionnaires. Constant–Murley score (CMS) and active ranges, forward flexion and external rotation, were also evaluated and documented. One year after surgery, ultrasound evaluation was done to determine the integrity of the rotator cuff for each patient. Results: The average age of enrolled patients at the time of surgery was 53.0 years (range, 40–59 years), and average follow-up was 16.6 months (range, 12–24 months). At 2 weeks, the range of forward flexion in the AA group was larger than that in the MO group (136.5 ± 10.2 vs 132.5 ± 7.7, P = 0.03). On postoperative day 1, the VAS in the MO group was significantly higher than that in the AA group (6.5 ± 0.6 vs 6.1 ± 0.6, P < 0.01). At 1 month, the difference in VAS between both groups reappeared (2.9 ± 0.6 vs 2.6 ± 0.6, P = 0.03). At 1 month, the CMS score of patients in the AA group was higher than that in the MO group (52.8 ± 3.6 vs 50.9 ± 5.0, P = 0.03). At 3 and 6 months, the DASH score of patients in the AA group was lower than that in the MO group (43.8 ± 8.2 vs 47.8 ± 4.4, P < 0.01 and 38.6 ± 4.3 vs 42.7 ± 9.9, P < 0.01, respectively). Mean operative time was longer in the AA group compared with that in the MO group (71.9 ± 17.6 vs 64.7 ± 12.7 minutes, P < 0.01). Five patients (10.0%) in the AA group and 4 patients (8.2%) in the MO group had rotator cuff retear, and 6 patients (12.0%) in the AA group and 8 patients (16.3%) in the MO group had adhesive capsulitis by the end of follow-up. There is no significant difference between the 2 groups in the incidence of complications. We also found that joint exercising at least 3 times per week was associated with better short- and long-term joint function recovery. Conclusions: The AA approach was associated with less pain and lower DASH score as well as higher CMS score in the early recovery period. No difference was found between the 2 groups in primary and secondary outcomes in the long term, or incidence of complications such as adhesive capsulitis and rotator cuff retear. In conclusion, we consider that the AA procedure has better recovery at short-term follow-ups, while both techniques are equivalent regarding long-term outcomes. Abstract : Supplemental Digital Content is available in the text